PENGARUH BEBAN, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PELAYANAN PAJAK PRATAMA CILEUNGSI - Aris Hidayat Kurniawan (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2019)
Oversight Office of Cileungsi First`th Tax Service seeks to improve the best service to commerce and community, through profesional service with quality work and better performance. There is still not optimal employee performance, it is thought the fact that there to be caused by a perceived high workload resulting in lower job motivation and job satisfaction of employees. Research conducted at Office of Cileungsi First’th Tax Service by taking 89 employees as the research sample. Data were collected by quitionnaire instruments covered by five rating scale from strongly disagree to strongly agree. Quantitative research was conducted by discribing and verification data. The Multiple linear regression analysis are the statistic approach to data analysis. Hypothesis testing are done by t-test and F-test. The study produced three major finding consistent with the hypothesis put forward, that are: 1) the workload of employees are in the high category, 2) work motivation is in the high category, 3) job satisfaction is in the high category and the performance is in the category of not bad. Base on research finding, in order to increase employee performance can be done by manage the workload of employees, increase work motivation and increase job satisfication. Kata kunci:Workload, Job Motivation, Job Satisfaction and Performance